2019
DOI: 10.3389/fphys.2019.00279
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Non-coding RNAs Network in Non-alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) spectrum comprises simple steatosis and non-alcoholic steatohepatitis (NASH) that can lead to fibrosis and cirrhosis. The patients usually have no history of excessive alcohol consumption and other etiologies that can cause fatty liver. Understanding of the pathophysiology of NAFLD has revealed that non-coding RNAs (ncRNAs) play significant roles in modulating the disease susceptibility, pathogenesis and progression. Currently, the ncRNAs are grouped according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 141 publications
1
58
0
Order By: Relevance
“…[1][2][3][4] Hepatic lipid metabolism is tightly regulated through a delicate interplay of hormones (such as insulin), nuclear receptors (such as LXR), numerous cellular signalling pathways (such as PI3K/AKT/ mTOR) and hepatic transcription factors (such as MLXIPL/ChREBP and SREBPs). [12][13][14][15] In this study, we investigated the role of lncRNA H19 in regulating hepatic lipid metabolism. Emerging evidence suggests that non-coding RNAs (ncRNAs), especially long non-coding RNAs (lncRNAs), may play an important role in liver metabolism and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Hepatic lipid metabolism is tightly regulated through a delicate interplay of hormones (such as insulin), nuclear receptors (such as LXR), numerous cellular signalling pathways (such as PI3K/AKT/ mTOR) and hepatic transcription factors (such as MLXIPL/ChREBP and SREBPs). [12][13][14][15] In this study, we investigated the role of lncRNA H19 in regulating hepatic lipid metabolism. Emerging evidence suggests that non-coding RNAs (ncRNAs), especially long non-coding RNAs (lncRNAs), may play an important role in liver metabolism and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the central dogma of the biology is that the information from the DNA is transcribed into the RNA and then are translated to proteins though, recent evidence shown that our genome consists of more ncRNAs than the protein-coding RNAs, and these ncRNAs are functional (Bertone et al, 2004;Djebali et al, 2012). These observations open up the new paradigm in understanding gene expression and regulation, particularly the multiple and diverse layers of molecular management of a single gene (Cipriano and Ballarino, 2018;Sulaiman et al, 2019). To date, various classes of the ncRNAs have been discovered.…”
Section: Noncoding Rnas (Ncrnas)mentioning
confidence: 99%
“…The importance of long noncoding RNA (lncRNA) has become a focus of hepatic lipid metabolism and fatty liver [21,22]. A large number of lncRNAs have been identified in the livers of NAFLD patients [23].…”
Section: Introductionmentioning
confidence: 99%